Miquelianin Inhibits Allergic Responses in Mice by Suppressing CD4+ T Cell Proliferation - Dae Woon Choi; Sun Young Jung; Gun-Dong Kim; So-Young Lee; Hee Soon Shin (MDPI AG, 2021)
Allergic diseases, including atopic dermatitis (AD), induce type 2 helper T (Th2) cell-dominant immune responses. Miquelianin (quercetin 3-O-glucuronide, MQL) is an active compound in Rosae multiflorae fructus extract with anti-allergic properties. Here, we investigate the anti-allergic effects of MQL in an ovalbumin (OVA)-induced Th2-dominant mouse model and the associated mechanisms. Oral MQL suppressed cytokine and IL-2 production and proliferation of Th2 cells and upregulated heme oxygenase-1 (HO-1) in splenocytes. Ex vivo MQL suppressed Th1- and Th2-related immune responses by inhibiting CD4+ T cell proliferation, and upregulated HO-1 in CD4+ T cells by activating C-Raf-ERK1/2-Nrf2 pathway via induction of reactive oxygen species generation. In a trimellitic anhydride-induced AD-like mouse model, both topical and oral MQL ameliorated AD symptoms by suppressing Th2 immune responses. Our results suggest that MQL is a potential therapeutic agent for CD4+ T cell-mediated diseases, including allergic diseases.